GEOMETRI ANALITIK BIDANG PADA KOORDINAT MIRING - Zainnur Wijayanto; Kusmanto kusmanto (Universitas Sarjanawiyata Tamansiswa, 2016)
The aim of this study was to determine (1) the shape and properties of any of the lines in the coordinate oblique, (2) the shape and properties of any of the circles on the coordinate oblique, (3) the shape and properties of any of parabola in oblique coordinates, (4) the shape and properties of any of the ellipse in oblique coordinates, (5) the shape and properties of any of the hyperbole in oblique coordinates.The method to be used is a literature review to collaborate with existing theories.The results showed that the equation of the line through p1=(x1-y1) and p2=(x2-y2) at oblique coordinate a becomes = y-y1 =mr(x-x1) with mr=tan (180-a) B mr=(y2-y1)/(x2-x1)